Cryopreservation of Sterlet Sperm (Acipenser ruthenus) Using DMSO-Based Cryoprotective Medium - Butskyi, Kirill I.; Puhovkin, Anton Yu.; Kopeika, Yevgeniy F. (Problems of Cryobiology and Cryomedicine, 2017)
Probl Cryobiol Cryomed 2017; 27(2):174.